A Human Gait Classification Method Based on Radar Doppler Spectrograms. (12th July 2010) - Tivive Tivive, Fok Hing Chi Fok Hing Chi; Bouzerdoum Bouzerdoum, Abdesselam Abdesselam; Amin Amin, Moeness G. Moeness G.
Abstract : An image classification technique, which has recently been introduced for visual pattern recognition, is successfully applied for human gait classification based on radar Doppler signatures depicted in the time-frequency domain. The proposed method has three processing stages. The first two stages are designed to extract Doppler features that can effectively characterize human motion based on the nature of arm swings, and the third stage performs classification. Three types of arm motion are considered: free-arm swings, one-arm confined swings, and no-arm swings. The last two arm motions can be indicative of a human carrying objects or a person in stressed situations. The paper discusses the different steps of the proposed method for extracting distinctive Doppler features and demonstrates their contributions to the final and desirable classification rates.